A Cohort Study of the Effects of Daily-Diet Water-Soluble Dietary Fiber on Butyric Acid-Producing Gut Microbiota in Middle-Aged and Older Adults in a Rural Region - Satoshi Sato; Daisuke Chinda; Tadashi Shimoyama; Chikara Iino; Sae Kudo; Kaori Sawada; Tatsuya Mikami; Shigeyuki Nakaji; Hirotake Sakuraba; Shinsaku Fukuda (Microorganisms, 2022)
Water-soluble dietary fiber is primarily a substrate for degradation of short chain fatty acids (SCFAs), particularly butyric acid, by gut microbiota. SCFAs have beneficial effects on the whole body. However, epidemiological studies on the association between water-soluble dietary fiber from daily food intake and butyric acid-producing bacteria are inconsistent. The purpose of this study was to determine the association between levels of water-soluble dietary fiber from daily food intake and gut microbiota, particularly butyric acid producers, in middle-aged and older adults in a rural area in Japan. We examined the effects of water-soluble dietary fiber intake on gut microbiota after adjusting for confounding factors. After propensity score matching, 520 subjects (260 in the low-intake group and 260 in the high-intake group) were selected. One year later after a follow-up survey, we re-classified the participants and again compared low- and high-intake groups. As a result, people with a high intake had a higher relative abundance of butyric acid-producing bacteria. It was also revealed that butyric acid-producing bacteria remained high in the group that maintained high intake the next year. We concluded that continuous intake of water-soluble dietary fiber from daily food is necessary to maintain sufficient amounts of butyric acid-producing bacteria.